On the merger of subsurface isolated vortices. Issue 1 (2nd January 2016) - Ciani, Daniele; Carton, Xavier; Verron, Jacques
Abstract : Vortex merger is a phenomenon characterizing the whole class of geophysical vortices, from atmospheric storms and large oceanic eddies up to small scale turbulence. Here we focus on the merger of subsurface oceanic anticyclones in an idealized primitive equations model. This study has been motivated by past and recent observations of colliding lens-like anticyclones off of Gibraltar Strait. The critical conditions for merger (critical merger distance and time needed for merger) are determined. We will show that the predictions of classical two-dimensional merger are not verified for subsurface isolated vortices. For instance, critical merger distances will be reduced because of the vortex potential vorticity (PV) structure. The post-merger characteristics of the vortex (radius, extension and PV), are also determined. Merger-related effects, like production of peripheral filaments and small-scale eddies are also investigated and suggest the contribution of merger in both direct and inverse energy cascades.